2018
DOI: 10.1016/j.hjc.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of the mitochondrial Na+/Ca2+ exchanger protects against ventricular arrhythmias in a porcine model of ischemia-reperfusion

Abstract: In a porcine model of myocardial infarction, intracoronary administration of CGP-37157 did not decrease IS or NRA. However, it suppressed ventricular arrhythmias, decreased depression of the J point during ischemia and expedited ST-segment resolution after reperfusion. These findings motivate further investigation of pharmacologic mNCX inhibition as a potential therapeutic strategy to suppress arrhythmias in the injured heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Ventricular tachycardia was prevented in vivo, and similar results were found in iPSC-derived human cardiomyocytes (Schweitzer et al, 2017). Furthermore, enhancing mitochondrial Ca 2+ content using the mNCX inhibitor CGP-37157 suppressed ventricular arrhythmias, lowered the depression of the J point during ischemia, and expedited ST-segment resolution after reperfusion in a porcine model of I/R (Sventzouri et al, 2018). Likewise, enhancing mitochondrial Ca 2+ transport using the mCU activator spermine in isolated rabbit atrial cardiomyocytes undergoing a tachypacing protocol to induce AF demonstrated a protective effect against Ca 2+ transient alternans.…”
Section: Regulation Of Mitochondrial Ca 2+ Transportsupporting
confidence: 58%
“…Ventricular tachycardia was prevented in vivo, and similar results were found in iPSC-derived human cardiomyocytes (Schweitzer et al, 2017). Furthermore, enhancing mitochondrial Ca 2+ content using the mNCX inhibitor CGP-37157 suppressed ventricular arrhythmias, lowered the depression of the J point during ischemia, and expedited ST-segment resolution after reperfusion in a porcine model of I/R (Sventzouri et al, 2018). Likewise, enhancing mitochondrial Ca 2+ transport using the mCU activator spermine in isolated rabbit atrial cardiomyocytes undergoing a tachypacing protocol to induce AF demonstrated a protective effect against Ca 2+ transient alternans.…”
Section: Regulation Of Mitochondrial Ca 2+ Transportsupporting
confidence: 58%
“…Finally, excessive mitochondrial Ca ++ efflux via mitochondrial NCX has been shown to increase oxidative stress and arrhythmias leading to SCD 192 . Pharmacologic inhibition of NCX with CGP‐37157 attenuates the incidence of ventricular arrhythmias, supporting a role of mitochondrial Ca ++ ‐related signaling in arrhythmogenicity 193 …”
Section: Targeting the Mitochondriamentioning
confidence: 98%
“…192 Pharmacologic inhibition of NCX with CGP-37157 attenuates the incidence of ventricular arrhythmias, supporting a role of mitochondrial Ca ++ -related signaling in arrhythmogenicity. 193 Several K + channels have been identified in the inner membrane of the mitochondria, such as the ATPdependent (mitoK ATP ), the voltage-gated Kv1.3 (mitoKv1.3), the calcium-activated (mitoBKCa) and the two-pore domain TASK-3 (mitoTASK) potassium channels. 194 They affect the integrity of the inner membrane and thus regulate mitochondrial functions, such as energy-transducing processes and ROS production.…”
Section: Mitochondrial Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In I/R, excessive Ca 2+ entry may be related to the Na + /Ca 2+ exchanger (NCX), and ablation of the NCX may protect against myocardial I/R injury [39]. Additionally, inhibition of the NCX may reduce the QT interval and arrhythmia [40, 41]. Previous studies showed that TLR4 activation may increase the expression of NCX, reduce the transient outward potassium current (Ito), and prolong the APD and QT interval [42, 43].…”
Section: Discussionmentioning
confidence: 99%